2004
DOI: 10.1074/jbc.m401901200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Kinetic Characterization of the DNA Helicase and Exonuclease Activities of Werner Syndrome Protein

Abstract: Werner syndrome is a human autosomal recessive disorder that displays symptoms of premature aging and an increased incidence of cancer (1). Cellular phenotypes of Werner syndrome include genomic instability (2-4), aberrant recombination (5-7), sensitivity to DNA-damaging agents (8 -11), and replication defects (12-14). The gene (WRN) defective in Werner syndrome encodes a protein that belongs to the RecQ family of DNA helicases (15) that includes four other human helicases, including the genes defective in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
59
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 53 publications
7
59
0
Order By: Relevance
“…In the WRN reactions, the unwound product migrated slightly faster than the heat-denatured DNA substrate control (Fig. 1F), consistent with earlier observations that WRN helicase product was slightly degraded by intrinsic WRN nuclease (31). The residual unwound product observed in WRN reactions containing BamHI-E111A migrated even slightly farther than the products from reactions lacking BamHI-E111A, suggesting further degradation by WRN nuclease when the helicase activity was blocked.…”
Section: Catalytically Inactive Bamhi Inhibits Dna Unwindingsupporting
confidence: 79%
“…In the WRN reactions, the unwound product migrated slightly faster than the heat-denatured DNA substrate control (Fig. 1F), consistent with earlier observations that WRN helicase product was slightly degraded by intrinsic WRN nuclease (31). The residual unwound product observed in WRN reactions containing BamHI-E111A migrated even slightly farther than the products from reactions lacking BamHI-E111A, suggesting further degradation by WRN nuclease when the helicase activity was blocked.…”
Section: Catalytically Inactive Bamhi Inhibits Dna Unwindingsupporting
confidence: 79%
“…Based on the crystal structures of the Bacillus stearothermophilus PcrA in the presence and absence of the nucleotides and DNA (19,20), Wigley and co-workers (20 -24) have found that the PcrA helicase functions as a monomer and that the structural and biochemical properties of the PcrA helicase are best explained by the "inchworm" mechanism. Consistent with this model, other helicases, such as UvrD (25), RecG (26), Dda (27,28), RecQ (29), BLM (30), WRN (31), and NS3h (32), could also function as a monomer. The crystal structures of NS3h (33), RecG (34), Rep (35), and E. coli RecQ (36) have revealed that these helicases are in the monomeric forms.…”
supporting
confidence: 51%
“…Similarly, atomic force microscopy analysis of a 171-amino acid fragment of WRN comprising the exonuclease domain of the enzyme revealed a trimer-hexamer equilibrium in the absence of DNA, with the equilibrium being significantly shifted toward the hexamer form in the presence of DNA (Xue et al, 2002). Thus, there remains an open question about the function and exact stoichiometry of the different WRN assembly states, even though recent kinetic experiments support a model where a monomeric unit is involved in DNA unwinding (Choudhary et al, 2004).…”
Section: Different Oligomeric States Of Recq Helicasesmentioning
confidence: 99%
“…1) (Huang et al, 1998;Mushegian et al, 1997;Shen et al, 1998). Recombinant WRN possesses 3Ј -5Ј exonuclease activity that can act on a wide variety of different substrates, much the same as its helicase function (Choudhary et al, 2004). This exonuclease domain can function independently of the rest of WRN polypeptide in that a recombinant fragment encompassing residues 1-333 displays exonuclease activity (Huang et al, 1998).…”
Section: Exonuclease Domain Of Wrnmentioning
confidence: 99%